KARAKTERISASI EKSTRAK TERPURIFIKASI KELOPAK ROSELLA (Hibiscsus sabdariffa L.) DAN AKTIVITASNYA SEBAGAI ANTIHIPERTENSI PADA TIKUS SPRAGUE DAWLEY - Fita Sari; Dyah Aryantini (As-Syifaa Jurnal Farmasi, 2020)
The characterization was ensuring quality of traditional raw materials for drug preparations. Purification extract was a part of extract which released from compounds it was more effective for pharmacological activities. The effectivity an antihypertensive was still very rarely proven by use of traditional ingredients, especially from purified rosella. The aim of the study is characterization and knowing of calyx purified extract of rosella which is suspected to have antihypertensive activity in vivo. The method was done by purifying, characterization, determined of quercetin, and antihypertensive activity. Positive control (captopril), negative (CMC Na 0,5%), test of 12,5 dan 25 mg/kg BB. Descriptive data analysis for characterization, linear regression analysis of quercetin and antihypertensive statistical testing. The results for characterization of 1.41% water content, specific gravity 0.63% w / v, drying losses 2.82% and 2.31%. Levels of quersetin of 7.02 ± 0.15. The activity as antihypertensive result decrease in blood pressure which is indicated by a significant difference between the positive control and the test group. The 25 mg / kg body weight ETKR dose is an effective dose in reducing blood pressure. The non-specific character of purified extract of rosella calyx, FHI and through oral administration of ETKR can reduce the blood pressure of test animals with an effective dose of 25mg / kgBB. This research still requires  identification of bioactive compounds responsible for these activities.